Pendidikan Humanis melalui Internalisasi Kurikulum Berbasis Cinta di Madrasah Aliyah Negeri - Afryansyah, Afryansyah; Sirozi, Muhammad (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to analyze the internalization of aspects of the Love-Based Curriculum (KBC) in Indonesian, English, and Arabic subjects. This study uses a descriptive qualitative approach through document analysis in the form of Lesson Plans (RPP) and Work Reference Framework (KAK) prepared by language teachers at MAN Insan Cendekia OKI. The results show that the internalization of the value of love is carried out through learning content and instructional strategies, for example, the selection of poetry texts, argumentative texts, and themes of everyday life. Of the six aspects of love formulated in the KBC, most have been integrated into the learning design, although implementation is still partial and requires strengthening in the aspects of love for the environment and the nation. These findings confirm that the KBC has relevance in developing humanist education in madrasas, but its success is highly dependent on teacher consistency and madrasa policy support.